Transverse Deformations and Structural Phenomenon as Indicators of Steel Fibred High-Strength Concrete Nonlinear Behavior - Iakov Iskhakov; Yuri Ribakov (Advances in Materials Science and Engineering)
As known, high-strength compressed concrete elements have brittle behavior, and elastic-plastic deformations do not appear practically up to their ultimate limit state (ULS). This problem is solved in modern practice by adding fibers that allow development of nonlinear deformations in such elements. As a rule, are applied steel fibers that proved high efficiency and contribute ductile behavior of compressed high-strength concrete (HSC) elements as well as the desired effect at long-term loading (for other types of fibers, the second problem is still not enough investigated). However, accurate prediction of the ULS for abovementioned compression elements is still very important and current. With this aim, it is proposed to use transverse deformations in HSC to analyze compression elements' behavior at stages close to ultimate. It is shown that, until the appearance of nonlinear transverse deformations (cracks formation), these deformations are about 5-6 times lower than the longitudinal ones. When cracks appear, the tensile stress-strain relationship in the transverse direction becomes nonlinear. This fact enables to predict that the longitudinal deformations approach the ultimate value. Laboratory tests were carried out on 21 cylindrical HSC specimens with various steel fibers content (0, 20, 30, 40, and 60 kg/m3). As a result, dependences of transverse deformations on longitudinal ones were obtained. These dependences previously proposed by the authors’ concept of the structural phenomenon allow proper estimation of the compressed HSC state up to failure. Good agreement between experimental and theoretical results forms a basis for further development of modern steel fibered HSC theory and first of all nonlinear behavior of HSC.